Women on boards and bank efficiency in ASEAN-5: the moderating role of the independent directors - Ramly, Zulkufly; Chan, Sok Gee; Mustapha, Mohd Zulkhairi; Sapiei, Noor Sharoja (Springer-Verlag Berlin Heidelberg, 2017)
Corporate governance codes around the world promote women’s presence in corporate board. The extant literature suggests women directors contribute to improve monitoring and advisory role of the board. This study aims to examine the role of independent women directors in improving banks’ efficiency. Using 102 commercial banks from ASEAN-5 countries for a period of 1999–2012, we run generalized method of moments models to test the relationship between the variables. Our results show that banks with independent women directors on board contribute significantly to the bank’s efficiency level. Contrary to the literature, we found that the appointment of women directors or independent directors alone does not significantly enhance banks’ efficiency. The result suggests that women directors are more effective on boards if they are also appointed as independent directors. This finding implies that a combination of corporate governance mechanism is more powerful than relying on a single element of corporate governance.